THE EXPRESSION OF GENDER IN LANGUAGES (ENGLISH AND UZBEK) - Matkarimova, Ashurkhon; Kamolova, Guljahon (International Conference on Linguistics & Translation, 2025)
This research presents a comparative study of how gender (as a socio-cultural construct) is expressed in English and Uzbek. It examines lexical, phraseological, pragmatic and discourse-level manifestations of gender, focusing on communicative settings (formal/informal interaction, media discourse, everyday speech). The study argues that while English tends to index gender more overtly through grammatical and lexical resources, Uzbek- despite lacking grammatical gender—actively encodes gender through address forms, evaluative vocabulary, cultural scripts, proverbs, and norms of polite interaction.